Understanding Manufacturing Informality: Employment and Productivity Linkages with the Formal Economy - Verma, Abhinav (H. : ĐHKT, 2020)
This paper on spatial economic relationships explores the possibility that the formal and informal sectors of an economy are deeply interconnected through buyer-supplier networks and through agglomeration effects. Looking at data on Indian manufacturing, this paper investigates employment and productivity linkages between formal and informal firms and refutes the classical theory of Economic Dualism. Linkages are estimated by using National Sample Survey and Annual Survey of Industries datasets that contemporaneously survey the informal and formal economy respectively at a nationally representative level. Data from 2001 and 2005 is used, and the unit of analysis is at the state-industry level. An OLS regression with fixed effects shows that a 1% increase in average form formal firm size in a particular state-industry category leads to a 0.083% increase in individual informal firm size. In terms of productivity, the impact of formal productivity in state-industry on informal productivity is positive but not significant.